Effect of Heat-Treatment on the Hardness and Mechanical Properties of Boron Alloyed Steel - Salwani, Mohd Salleh; Mohammad Raffik, Khiyon (2016)
In an automotive industry, hot stamped, die quenched structural components have been widely used to provide extra protection against crash intrusion. Boron alloyed steel exhibit limited ductility, but it also promotes improvement in impact performance. This study analyzed the effect of cooling rate on the hardness and energy absorption. Selfquenched specimens were heated to 850°C and cooled in air of room temperature, water at room temperature and cold water. Vickers hardness test and tensile test was then carried out to analyze the effect of different quenching rate. Self-quenched specimens were compared to the properties of the die-quenched specimens obtained from commercial automobile body. Result shows that boron steel with the highest cooling rate has the highest value of hardness but low in strength.